2010
DOI: 10.1038/jhg.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of apolipoprotein A5 SNPs and haplotypes on triglyceride concentration in three ethnic origins

Abstract: Several polymorphisms in the ApoA5 gene emerged as important candidate genes in triglyceride metabolism. The aim of this study was to determine the associations between ApoA5 polymorphisms, plasma triglyceride concentrations and the presence of cardiovascular disease (CVD) in three ethnic origins. Genotypes for 15 single nucleotide polymorphisms (SNPs) were determined in 659 older adults (mean age 71 ± 7 years) who immigrated to Israel or whose ancestors originated from East Europe (Ashkenazi), North Africa, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…The other important confirmation in our findings was the robust association of TG concentrations in this cohort with rs964184 from the inter-genic region between BUD13 and ZNF259, and rs12286037 an intronic variant from ZNF259 near APOA5-A4-C3-A1 . The APOA5-A4-C3-A1 locus is associated with plasma TG and VLDL-C levels in several studies including Caucasian GWAS and meta-analyses [8], [18], Chinese [19], Asian Indians from UK [20], US Whites and Blacks [21], and Middle-Easterns [22]. Notably, in our study, the allelic effects of these variants were stronger under conditions of dyslipidemia associated with T2D and the difference in effect size (β = 0.16 T2D vs. β = 0.10 NG control) for rs964184 was statistically significant (p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…The other important confirmation in our findings was the robust association of TG concentrations in this cohort with rs964184 from the inter-genic region between BUD13 and ZNF259, and rs12286037 an intronic variant from ZNF259 near APOA5-A4-C3-A1 . The APOA5-A4-C3-A1 locus is associated with plasma TG and VLDL-C levels in several studies including Caucasian GWAS and meta-analyses [8], [18], Chinese [19], Asian Indians from UK [20], US Whites and Blacks [21], and Middle-Easterns [22]. Notably, in our study, the allelic effects of these variants were stronger under conditions of dyslipidemia associated with T2D and the difference in effect size (β = 0.16 T2D vs. β = 0.10 NG control) for rs964184 was statistically significant (p = 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that remnant lipoproteins, among TG-rich lipoproteins, induce EGFR phosphorylation in smooth muscle cells, which results in smooth muscle cell proliferation and atherosclerosis risk [16] and that EGF concentrations in plasma and peripheral blood mononuclear cells associate with lipid concentrations, including TG and HDL-C [17]. Furthermore, the variants exerting effects on TG and HDL-C levels, including rs662799, rs3135506, rs651821, rs2072560, rs2266788, rs6589566, and rs964184, cluster together and are in strong linkage disequilibrium (LD) with each other around the two genes [3,18,19]. Therefore, construction of haplotypes with variants spanning both genes is necessary to estimate the precise TG-elevating and HDL-C-lowering effects of APOA5 SNPs in a population.…”
Section: Introductionmentioning
confidence: 99%
“…APOA5 indirectly regulates TG metabolism by stimulating the lipoprotein lipase (LPL) activity, which increases the rate of LPL-mediated TG 30) . In previous genotyping and haplotyping studies, the APOA5 gene was reported to be associated with an elevated TG level; however, the clinical significance and prevalence varied among different ethnicities [31][32][33][34][35][36][37][38][39] . In Taiwan, two haplotypes of APOA5 (rs662799 and rs2075291) have been found to be closely related to HTG 39) .…”
Section: Discussionmentioning
confidence: 99%